ARTISTIC WORLD OF DRAMA OF IVAN ZUBENKO «THE LAST VICTIM»: TEXT AND CONTEXT - Kasyanenko, T. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The genre specific of stage texts is first outlined and on this basis the stages of dramaturgic creative growth of known are certain in Galichina in 20-30 ХХ age of journalist, poet and writer, dramatist, publicist and public-cultural figure Ivan Zubenko. Its artistic world and problems of construction of dramaturgic conflict and design of character turn out on material of drama the «Last victim». Dramaturgy of artist of word is first entered to the in general lines Ukrainian literature-art process of the noted period.